In vitro antimicrobial properties of a mouthrinse containing glycerine, potassium nitrate and sodium fluoride - Ndlovu, Nozizwe (My University, 2008)
ABSTRACT Introduction: Patients who have received radiation therapy due to oral cancers often present with complications such as salivary dysfunction, mucositis, soft tissue necrosis, infections and dental caries. The aim of this study was to investigate the antimicrobial properties of an experimental mouthrinse which also contains analgesic and anticaries compounds and can be used in the management of patients with oral cancers after radiation therapy. Methods: The experimental mouthrinse contained a mixture of 30% glycerine (antimicrobial agent), 7% potassium nitrate (analgesic) and 0.025% sodium fluoride (anticaries agent). The minimal inhibitory concentration (MIC) of these ingredients was tested against Candida albicans, Staphylococcus aureus and Streptococcus mutans over 24 hours at different concentrations. MICs of commercially available mouthrinses containing chlorhexidine digluconate (Corsodyl®) and fluoride with triclosan (Plax®) were also determined using the same organisms. All mouthrinses were then tested to determine the percentage kill over 1, 2, and 3 minutes. The costs of these mouthrinses were also compared. Results: The MICs for glycerine were 10%, 25% and 10% for C. albicans, S. aureus and S. mutans respectively. Potassium nitrate, sodium fluoride and alum did not show any antimicrobial effects. The MIC of Corsodyl® was <0.02 mg/ml for all the test organisms. The MIC for Plax was 0.02 mg/ml, <0.002 mg/ml and 0.005 mg/ml for C. albicans, S. aureus and S. mutans respectively. Combining glycerine, potassium nitrate and sodium fluoride into a mixture did not affect the antimicrobial properties of these constituents. The mixture killed 99.78%, 99.88% and 99.98% of C. albicans, 61.74%, 70.64% and 85.09% of S. aureus and 91.72%, 99.47% and 99.99% of S. mutans after 1, 2 and 3 minutes respectively. Two percent chlorhexidine digluconate killed 98.98%, 99.97% and 99.99% of C. albicans, 95.83%, 99.68% and 99.97% of S. aureus and 99.98%, 99.96% and 99.99% of S. mutans after 1, 2 and 3 minutes respectively. Plax® killed 99.99% of C. albicans in one minute, 99.66%, 99.99% of S. aureus in 1 and 2 minutes respectively; and 99.89%, 99.96% and 99.99% of S. mutans in 1, 2 and 3 minutes respectively. The costs of similar amounts of the experimental mouthrinse, Corsodyl® and Plax® were R5.24, R30.00 and R10.00 respectively. Conclusion: A mouthrinse effective in relieving oral symptoms in patients receiving radiation therapy needs to show some antimicrobial activity against in particular, C. albicans and S. mutans, whilst at the same time having a palliative effect. This study has shown that the experimental mouthrinse will fulfil these requirements. The experimental mouthrinse was found to be the cheapest in comparison to Corsodyl® and Plax®.
Keywords: mouthrinse; antimicrobial mouthrinse properties